Nitrous oxide in the North Atlantic Ocean - Walter, S.; Bange, H. W.; Breitenbach, U.; Wallace, D. W. R. (CCSD, 2006)
International audience In order to investigate the role of the North Atlantic Ocean as a source of atmospheric nitrous oxide and to decipher the major formation pathways of nitrous oxide, measurements of dissolved nitrous oxide were made during three cruises in the tropical, subtropical and subpolar North Atlantic in October/November 2002, March/April 2004, and May 2002, respectively. Nitrous oxide was close to equilibrium or slightly supersaturated in the surface layers suggesting that the North Atlantic acts as a weak source of nitrous oxide to the atmosphere. Depth profiles showed supersaturation throughout the water column with a distinct increasing trend from the subpolar to the tropical region. Lowest nitrous oxide concentrations, near equilibrium and with an average of 11.0±1.7 nmol L ?1 , were found in the subpolar North Atlantic where the profiles showed no clear maxima. Highest values up to 37.3 nmol L ?1 occurred in the tropical North Atlantic with clear maxima at approximately 400 m. A positive correlation of nitrous oxide with nitrate, as well as excess nitrous oxide with AOU, was only observed in the subtropical and tropical regions. Therefore, we conclude that the formation of nitrous oxide occurs in the tropical region rather than in the subpolar region of the North Atlantic and suggest nitrification is the dominant formation pathway in the subtropical and tropical regions.